2015
DOI: 10.4236/ajac.2015.66050
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Fluxes and Sediments Composition in El Mex Bay and Surround Drains, Alexandria, Egypt

Abstract: The regeneration of pore water (PW) nutrients was investigated and the contribution of benthic nutrient fluxes to the overlying bottom water (BW) was examined. Dissolved inorganic nutrients (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is found that the amount of phosphate in the seawater is small compared with that of waste waters. This is probably due to the deposition and migration of phosphorus from overlying water to the sediment [16,45], the high rate of consumption at the surface layer by organisms [33], the slow rate of regeneration of phosphate from underlying sediment [33,35], and the influence of the distribution of phosphate within the surface layers of natural waters [44].…”
Section: Nutrient Saltsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the amount of phosphate in the seawater is small compared with that of waste waters. This is probably due to the deposition and migration of phosphorus from overlying water to the sediment [16,45], the high rate of consumption at the surface layer by organisms [33], the slow rate of regeneration of phosphate from underlying sediment [33,35], and the influence of the distribution of phosphate within the surface layers of natural waters [44].…”
Section: Nutrient Saltsmentioning
confidence: 99%
“…This owing to high effect land-based sources (i.e. sewage, agriculture, and/or industrial effluents) [16,26], the increase of regeneration rate of silicate from underlying sediments, the decomposition and death of diatom [35], and the low rate of the uptake of silicate by microorganisms especially diatoms. This is strongly supported by the low count of diatoms in Abu-Qir Bay [26,45].…”
Section: Nutrient Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of water masses and circulation in El-Mex Bay control the accumulation, distribution, and flux of wastewater (Alam El-Din, 2001; Farag, 2009), which are in turn affected by the continuous alteration in the morphology of the bay due the extensive constructions of new infrastructures. Shreadah et al, 2014;2015a), the winter-closure period (in January and February) leads to accumulation of pollutants in the drain, and the wastewater in the canals is subjected to strong unsteady flow, while a relatively stable flow occurs from June to October.…”
Section: Spatiotemporal Variation Of Water Qualitymentioning
confidence: 99%
“…The pond of oxidation has attempted to be one of the most important affordable waste treatment methods for small isolated industrial and community units in African country (Mahajan et al, 2009). The existence of bacterial species is more (Kogo et al, 2017), beside to the diversity of fungi-classification (Masoud et al, 2016), and algal-classification (Shreadah et al, 2015;Henry et al, 1987), in addition to protozoa-classification (Abd-Elhamied, 2020;Tembhre & Kumar, 1997), and virus-classification (Shaltout et al, 2019). The microbiological solids produced by the algae on the pond impact total suspended solids (TSS) and biochemical oxygen demand (BOD) in effluent (Tuleibah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%